EVALUATION OF THE 'INDONESIA GEMILANG' COMMUNITY EMPOWERMENT PROGRAM BY LAZ Al-AZHAR IN CILEMBU VILLAGE - Dwiputrianti, Septiana; Rangkuti, Rina Andriani; Pratiwi, Arundina Dijah Retno; Mursalim, Siti Widharetno (Sultan Syarif Kasim State Islamic University, Riau, 2024)
This research evaluates the